How does nitrogen and forage harvest affect belowground biomass and nonstructural carbohydrates in dual‐use Kernza intermediate wheatgrass?. Issue 5 (7th August 2020) - Sakiroglu, Muhammet; Dong, Chenfei; Hall, Mary Beth; Jungers, Jacob; Picasso, Valentin
Abstract: Intermediate wheatgrass [ Thinopyrum intermedium (Host) Barkworth & D.R. Dewey] is a cool‐season perennial forage grass, whose grain is commercialized in the United States as "Kernza." Its extensive root system may help in reducing soil erosion, water pollution, and C emissions. Nitrogen fertilization and forage harvest intensity may affect the belowground biomass and nonstructural carbohydrate (NSC) concentrations, which may affect growth in subsequent years. We compared N doses and forage harvest treatments in a replicated complete block experiment in three environments (location‐years: Arlington, WI, 2016 and 2017; and St. Paul, MN, 2016). Seeds were sown in the fall, Kernza grain was harvested in the following summer, and rhizomes and roots were sampled in fall to a depth of 0.1 m over 2 yr. The water‐soluble carbohydrates (WSC) accounted for 97–99% of NSC, across environments. The WSC concentration was higher in rhizomes than in roots in both years, but WSC mass was higher in roots than rhizomes due to greater root biomass. Nitrogen generally did not change NSC concentrations across years, but reduced WSC in rhizome the second year in WI. Forage harvest did not affect NSC concentrations across locations and years. Belowground biomass to 1‐m depth in the fall of the second year in Wisconsin averaged 478.3 g m −2 regardless of treatment. Summer forage yield in the following year was positively associated with root biomass in the fall. These results suggest that harvesting forage in a Kernza dual‐use system is not detrimental to intermediate wheatgrass above‐ and belowground productivity.